دراسة ترب الموليسول في المنطقة الساحلية السورية - رقيه, عادل (Latakia University Journal -Biological Sciences Series, 2019)
بينت دراسة الغطاء البيدولوجي في المنطقة الساحلية أن ترب الموليسول تعتبر مكونا أساسيا في تركيب هذا الغطاء، على مختلف الصخور الكلسية وتحت مختلف الأغطية النباتية. إن وجود هذه الترب في منطقة يزيد معدل هطولها عن 1000 مم/السنة وفي ظل حرارة موجبة على مدار العام يدل على حداثة هذه التربة وعلى أنها عديدة التشكل Polygenesis. من الناحية التصنيفية لم يلاحظ إلا تحت رتبة Rendolls وهي التربة الأقل تطورا ضمن رتبة الـ Mollisol، أما من حيث الخواص المنشئية فلم تصل بعد لحالة الثبات Steady State بالنسبة لعوامل تكوينها. تعتبر ترب الموليسول ذات خواص فيزيائية وكيميائية جيدة، ويساعد وجود كربونات الكالسيوم في الحفاظ على المادة العضوية والعناصر الغذائية. We found In a previous study of the Structure of pedologic Cover in the Coastal Region of Syria that Mollisol soils are one of the essential components of this cover. Mollisol soils occur on different calcium rocks and also under several vegetation types. The occurrence of those soils in a region with precipitation over 1000 mm/year and positive temperature all over the year indicates that those soils are new and Polygenesis. From the classification point of view we only found the under order Rendolls which considers the less developed soil in the order Mollisol. Regarding the evolutional characteristics we can say Rendolls didn’t reach until now the steady state. Mollisol has good physical and chemical properties, the presence of calcium carbonate helps in preserving of organic matter and nutrient elements.